Highly efficient sulfimidation of 1,3-dithianes by Cu(I) complexes - Giribabu, Lingamallu; Singh, Surya P.; Patil, Nandkumar M.; Kantam, M. Lakshmi; Gupte, Sunil P.; Chaudhari, Raghunath V. (Synthetic Communications, 2008)
A series of four Cu(I) complexes were tested for sulfimidation of 1,3-dithianes in the presence of [N-(p-tolysulfonyl)imino]phenyliodinane (PhI = NTs) as the nitrene-transfer agent. Cu(TMPhen)(PPh3)Br is an efficient catalyst with more than 90% yield of the corresponding product with less reaction time as compared to the literature copper(I) complexes.
Keywords: 1; 3-dithianes; Cu(I) complexes; PhI = NTs; sulfimidation

Heterogenized copper catalysts for the amination of arylhalide: synthesis, characterization and catalytic applications - Patil, Nandkumar M.; Gupte, Sunil P.; Chaudhari, Raghunath V. (Applied Catalysis A-General, 2010)
This research investigated the synthesis, characterization and catalytic activity of heterogenized copper complexes for the selective amination of aryl halides. Amination reactions using homogeneous copper catalyst systems are not generally selective and it is also difficult to recover the catalyst from the homogeneous system for recycling. To overcome these difficulties, our efforts were directed towards the development of cheaper heterogeneous catalyst systems, which can be easily recovered and recycled. Heterogenized analogs of the homogenous Cu complexes were prepared using two methods: (a) encapsulation of copper complexes in zeolite-Y and (b) tethering of copper complexes on various supports like zeolite-Y, silica, charcoal, or clay. The encapsulated and tethered copper catalysts on zeolite-Y were characterized using EPR, Diffused reflectance UV-vis, XRD, IAS, ICPES, SEM, and TEM. The results confirmed that the copper complexes were truly heterogenized in zeolite-Y support. Encapsulated and tethered copper complexes were tested for amination of aryl iodide. The effects of various reaction parameters were examined using tethered Cu(Phen)(PPh(3))Br-PTA-Y catalyst to determine optimum conditions. A recycle study of encapsulated and tethered Cu catalyst was carried out to test their robustness for possible commercial exploitation. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Amination; C-N coupling; Copper; heterogeneous catalysis; mesoporous materials